Analisa Struktural Batuan Andesit di Desa Laksanamekar Bandung Jawa barat - Handoyo Saputro; Puji Hariati Winingsih (Jurnal Fisika FLUX, 2019)
This article discusses structural analysis in Laksanamekar Village, Bandung. The sample is in the form of andesite D and A *. Sample size (1 x 1) cm, with thickness (x) 0.4 cm. Sample D comes from the mountains of Laksanamekar Village Bandung at depths (15-20) m and samples (A *) from the Code River Yogyakarta. The results showed that the sample was a type of dry andesite rock and had layers in the grain. Andesite D has a denser composition, higher iron content and smoother surface texture than A*. The XRD results are known to be phase-identified andesite A * Sodium aluminum Silicate with a composition of 46.5% and andesite D phase of Titanium Calcium Sodium Magnesium Iron Manganese Silicon Aluminum Oxide of 10% so that andesite rocks have higher quality than A * samples.